Evaluating Midwives’ Knowledge and Attitudes Regarding Pre-Eclampsia Management at Presbyterian Hospital (London Journal of Medical and Health Research, 2026)
Background: Pre-eclampsia is a major contributor to maternal and perinatal morbidity and mortality globally and in Ghana. Midwives play a critical role in the early detection and management; however, their knowledge, attitudes, and the challenges they encounter influence the quality of care. Methodology/Principal Findings: A descriptive cross-sectional study was conducted among 50 midwives using a structured self-administered questionnaire. Data were analyzed using SPSS version 26. Descriptive statistics summarized demographic characteristics, knowledge, attitudes, barriers, and recommendations. Chi-square tests and logistic regression examined associations between demographic variables and knowledge/attitude levels. The majority of respondents were aged 20–39 years (70.0%), with 54.0% having 1–3 years of experience, and 86.0% had received prior training in pre-eclampsia management. Knowledge was generally high, with 88.0% recognizing hallmark symptoms and 84.0% identifying magnesium sulfate as the first-line anticonvulsant. Attitudes were positive; 68.0% strongly agreed that pre-eclampsia training should be mandatory. Key barriers included limited patient awareness (86.0%), understaffing (70.0%), and inadequate diagnostic tools (58.0%). Years of experience were significantly associated with knowledge level (chi-square = 19.470, p=0.003), while logistic regression showed work unit as a significant predictor of knowledge level (p = 0.037). Conclusion: Midwives exhibited good knowledge and positive attitudes toward pre-eclampsia management, though systemic barriers constrain effective care. Strengthening in-service training, improving diagnostic and therapeutic resources, and enhancing patient education are recommended to optimize outcomes.
Keywords: Attitudes; barriers; Ghana.; knowledge; Midwives; Pre-eclampsia (PE)